AKHTᾹ’ YAJIBU AN TUSAHHAHU: AKHTᾹ’ NAHWIYYAH WA USLŪBIYYAH WA IMLᾹIYYAH FI KURRᾹSᾹTIT TADRĪB LI TALABATIL MADRASATIL IBTIDĀIYYAH - Faris Maturedy; Wihdatul Hasanah; Muhammad Alfan (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2021)
Teaching materials are an important element in the learning process, especially in learning Arabic. These teaching materials can be taken from various learning sources. One of the learning resources that teachers often use is student worksheets. However, there were several errors in the Arabic worksheet entitled "Ilham" which was studied by third grade students at the Islamic elementary school level. This study aims to describe the errors in teaching materials in the form of worksheets in basic Arabic subjects. Therefore, this research is important because material is an element that cannot be negotiated. This research uses descriptive qualitative method. Data obtained through documentation. Then the data obtained were analyzed using the Miles & Huberman model. The results of this study indicate that the errors in the Ilham Arabic LKS class III lie in the aspects of grammar, uslub, morphology and imla'. The number of grammatical errors was 29. Uslub's number of errors was 3. Morphological errors were 3 errors. Grammatical and imla 'errors amount to 4 errors. Keywords: Teaching mateials, error analysis, Arabic Learning, Student worksheet